Mitigation strategies for heat-related illness during mass gatherings: Hajj experience - Almuzaini, Yasir; Alburayh, Marriyah; Alahmari, Ahmed; Alamri, Fahad; Sabbagh, Abdulrahman Y.; Alsalamah, Majid; Khan, Anas (Frontiers in Public Health, 2022)
Introduction: To mitigate morbidity, mortality, and impacts of Heat related illnesses (HRIs) on health, it was vital to implement a comprehensive framework for HRIs prevention and control. A recognized tool from the field of trauma prevention known as the Haddon matrix was applied. The matrix states that any event is affected by three factors: host, agent, and environment. In addition, another recognized tool known as the combined model was used in this study. The combined model is a three-dimensional model that includes the idea for the three axes of Haddon’s matrix with the methodology of the community risk reduction model (CRR). Aim of the study: To identify the environmental and individual risk factors of HRIs based on the Haddon Matrix and the recommended prevention strategies by the CRR tool by using the combined model. Methodology: An extensive literature review was conducted to assess all the risk factors associated with heat-related illnesses, as well as preventive measures. Then the Haddon matrix was used to structure, separating human factors from technical and environmental details and timing. After that, the combined model was used to set all responses and mitigation measures for each element obtained from the Haddon matrix tool. Conclusion: Projected increases in heat stress over globe requires the formulation and implementation of evidence-based HRIs mitigation and preventive measures. In this study we implemented the combined model that utilized as a systematic strategy for the more theoretical framework of Haddon’s matrix. Using Haddon matrix to determine the HRIs risk factors and the combined model to mitigate its impact was practical and helpful in planning, preparedness and mitigating of the HRIs during Hajj, and provided a broad approach equivalent to the Swiss cheese model and would facilitate informed decision. Keywords: Heat related illnesses, Haddon Matrix Tool, Community Risk Reduction Tool, Combined Model, Mass gatherings, Hajj